Role of Ijtihad in Islamic Law of Succession: Wasiyyat Wajibah as A Case Study - Nafiu Ahmed Arikewuyo (IJISH (International Journal of Islamic Studies and Humanities))
Ijtihād , which is the utilization of a Muslim jurist’s sense of reasoning to determine the legal status of an action under the Shari’ah, has played a major role in widening the scope of Islamic law and in making it responsive to the unending human problems and needs. The aspect of succession in Islam has been a discipline, which common Muslims have always believed that its content has been fully addressed by the texts in exclusion of juristic polemics. Hence, the current study aims to assert the role of Ijtihād  in the subject, using waṣiyyat wājibah (compulsory will) as a case study. The study adopts a qualitative method in reaching its submissions. It discovers that Ijtihād  has played a major role in the development of mirath across ages. It also asserts that waṣiyyat wājibah  is a product of both neo-Ijtihād  and collective Ijtihād  which is prone to further assessment of its validation, particularly in regions which do not share same experience with the Arabo-Muslim nations where it is legislated. The study recommends further research into how Ijtihād has developed the contents of mirath.